Phylogenetic relationships of Mathewsia and Schizopetalon (Brassicaceae) inferred from nrDNA and cpDNA regions: Taxonomic and evolutionary insights from an Atacama Desert endemic lineage. Issue 2 (27th December 2018) - Toro-Núñez, Oscar; Mort, Mark E.; Ruiz-Ponce, Eduardo; Al-Shehbaz, Ihsan A.
Abstract: Mathewsia (6 spp.) and Schizopetalon (10 spp.) are sister genera of the tribe Schizopetaleae (Brassicaceae, Cruci ferae). The genera are mostly endemic to Chile and neighboring areas of Peru and Argentina, with most species growing in the hyperarid Atacama Desert and adjacent areas. This geographic distribution and the presence of different life forms in Mathewsia (perennial) and Schizopetalon (annual) provide the opportunity to compare patterns of diversification under ex treme environmental pressure. In this paper, phylogenetic relationships are estimated for 17 species using a combination of two nuclear regions (rDNA ITS+ETS) and four plastid regions ( atpI–atpH, trnQ–rps16, trnH–psbA spacers, and rps16 intron) using maximum parsimony, maximum likelihood, and Bayesian approaches. Analyses of the combined cpDNA and the combined nrDNA result in topologies that are highly similar, although several instances of topological incongruence are noted. Results from all three criteria and all datasets support the monophyly of Schizopetalon, but not of Mathewsia . Mathewsia is rendered non–monophyletic because M. nivea is placed outside of Schizopetaleae ( Mathewsia+Schizopetalon ); a result that is also sup ported by morphology. The monophyly of some species is confirmed; however, several currently recognized species were not recovered as a clade and will require additional study. Further analyses are needed to resolve the placement of M. nivea and the origins of discordant nuclear and plastid signal.